Learning about ones' self - Yves Le Yaouanq; Peter Schwardmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
How can naivete about present bias persist despite experience? To answer this question, our experiment investigates participants' ability to learn from their own behavior. Participants decide how much to work on a real effort task on two predetermined dates. In the week preceding each work date, they state their commitment preferences and predictions of future effort. While we find that participants are present biased and initially naive about their bias, our methodology enables us to establish that they are Bayesian in how they learn from their experience at the first work date. A treatment in which we vary the nature of the task at the second date further shows that learning is unencumbered by a change in environment. Our results suggest that persistent naivete cannot be explained by a fundamental inferential bias. At the same time, we find that participants initially underestimate the information that their experience will provide - a bias that may lead to underinvestment in experimentation and a failure to activate self-regulation mechanisms.
Keywords: D83; D90; 330; naivete; present bias; learning